Cultivation of Chlorella sp. for biodiesel production using two farming wastewaters in eastern Colombia (2021)
The production of biofuels using wastewater as a microalgae culture medium is a little explored technology, but with potential for success. In order to contribute to the knowledge of these technologies and their technical feasibility for microalgae growth, in this work the Chlorella sp. strain was cultivated in two types of effluents generated in an experimental farm located in eastern Colombia, before and after a biological treatment process. The consumption of the main nutrients that regulate growth and lipid production was evaluated, in order to extract, quantify, characterize and convert them into biodiesel. The results showed that Chlorella sp. growth and lipid production is more favourable in R2 medium of treated water than in R1 medium of raw water, mainly due to phosphorus limitation and higher N-NO3 concentration in R2 compared to R1. In the R2 medium culture, a percentage of 42.54% of long-chain fatty acids was found, which is necessary to obtain a high quality biodiesel. Finally, the best transesterification experiment allowed reaching a fatty acid methyl esters (FAME) percentage of 90.1 ± 2.7%. In general, the results demonstrated the potential viability of using the wastewater generated in the San Pablo farm to produce biomass with lipid content to obtain biodiesel, finding that where the concentration of nutrients, mainly nitrogen, has a great influence on the microalgal metabolism for lipid accumulation.